2015
DOI: 10.1095/biolreprod.115.129718
|View full text |Cite
|
Sign up to set email alerts
|

CYP26 Enzymes Are Necessary Within the Postnatal Seminiferous Epithelium for Normal Murine Spermatogenesis1

Abstract: The active metabolite of vitamin A, retinoic acid (RA), is known to be essential for spermatogenesis. Changes to RA levels within the seminiferous epithelium can alter the development of male germ cells, including blocking their differentiation completely. Excess RA has been shown to cause germ cell death in both neonatal and adult animals, yet the cells capable of degrading RA within the testis have yet to be investigated. One previous study alluded to a requirement for one of the RA degrading enzymes, CYP26B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 35 publications
6
57
0
Order By: Relevance
“…Because both an excess and lack of RA are detrimental for most tissues, regulation of its concentration by CYP26 enzymes needs to be appropriately controlled (56)(57)(58)(59)(60). In the seminiferous epithelium, the major CYP26 enzyme that hydrolyzes RA is CYP26B1 (18,32). However, despite its importance for RA degradation in the testis, the molecular control of spatiotemporal CYP26B1 expression is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because both an excess and lack of RA are detrimental for most tissues, regulation of its concentration by CYP26 enzymes needs to be appropriately controlled (56)(57)(58)(59)(60). In the seminiferous epithelium, the major CYP26 enzyme that hydrolyzes RA is CYP26B1 (18,32). However, despite its importance for RA degradation in the testis, the molecular control of spatiotemporal CYP26B1 expression is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult testis, CYP26B1 is produced by peritubular myoid cells (68) and at a lower level by Sertoli cells and germ cells. Elimination of its activity within both germ cells and Sertoli cells induces loss of germ cells and severe subfertility, demonstrating a clear function for this enzyme in the adult seminiferous epithelium (32). Although the question of which cells produce RA in the adult seminiferous epithelium is still debated, it has been recently demonstrated that Sertoli cells produce RA necessary for the transition between A undiff and A diff spermatogonia, whereas midpachytene spermatocytes produce the RA necessary for induction of the meiotic prophase, spermatid elongation, Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Independent of the nuclear RAR/RXR response, it appears that a primary consequence of RA stimulation of progenitor spermatogonia is to induce translation of mRNAs encoding the KIT tyrosine kinase and STRA8, via a mechanism involving P13K/AKT/mTORC1 signaling (Busada et al 2015a, b). Recent conditional mutants of CYP26A1 and CYP26B1 within either Sertoli cells (Amh-Cre) or differentiating spermatogonia (Stra8-iCre) suggest that neither enzyme is essential for spermatogenesis, since these animals were fertile (Hogarth et al 2015b). It is not clear why only some undifferentiated spermatogonia respond to RA, although it is possible that expression of CYP26A1 and CYP26B1 enzymes, which catalyze the degradation of RA, may restrict RA action to subpopulations of progenitor spermatogonia.…”
Section: Retinoic Acidmentioning
confidence: 99%